2010
DOI: 10.1115/1.4000764
|View full text |Cite
|
Sign up to set email alerts
|

Twinkling Phenomena in Snap-Through Oscillators

Abstract: Oscillatory behavior in a chain of masses connected by springs with continuous but non-monotonic spring forces can be induced under quasi-static loading. Insight into the birth of this behavior is obtained from a single mass system. A bifurcation study shows the potential for equilibrium jumps between multiple equilibria. As such, the transients occurring under quasi-static loading do not converge to the static loading case. Transients during dynamic loading show sensitivity to the loading parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…2(a), which results in a chain of particles grounded nonlinearly and in a bistable onsite potential [247]. Again, small, moderate, and large excitations of the chain will result in, respectively, linear, weakly nonlinear, and strongly nonlinear wave motion [248].…”
Section: Multistability and Nonlinear Metamaterialsmentioning
confidence: 99%
“…2(a), which results in a chain of particles grounded nonlinearly and in a bistable onsite potential [247]. Again, small, moderate, and large excitations of the chain will result in, respectively, linear, weakly nonlinear, and strongly nonlinear wave motion [248].…”
Section: Multistability and Nonlinear Metamaterialsmentioning
confidence: 99%
“…This model is an excellent model to mimic the experiment since both the lengths and the radii of the magnets are in the order of 0.01 meters and the minimum distance d m between the magnet centers is on the order of the length l m of the magnets. Using the magnetic force, from equation (11), between the fixed and oscillating magnets of the twinkler and the spring forces from equation (1), the governing equations of motion of the SDOF nonlinear energy generator are represented in equation (15).…”
Section: Numerical Simulation Of the Twinkling Energy Generatormentioning
confidence: 99%
“…To be able to harvest such energy, it is critical to understand the underlying dynamics of the coupled snap-through oscillators. Several authors have studied the dynamics of various snap-through negative-stiffness and bistable systems [1]- [8]. Vibration-based energy harvesting from linear systems [9], [10] has been optimized experimentally [11]- [13] by tuning the forcing frequency to the natural frequency of the oscillator.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous results have shown that chains of elements with nonmonotonic (piecewise-linear) forcedisplacement relations can dissipate energy at a fast rate by transforming kinetic energy into high-frequency oscillations (so-called twinkling modes). This was later extended to chains with smooth nonmonotonic force-displacement relations in a comprehensive stability analysis [75]. It was also experimentally demonstrated in chains of granular particles with a nonsmooth contact interaction [76].…”
Section: Introductionmentioning
confidence: 99%
“…[75] and references therein. Here we disregard just oscillations and focus on the propagating kink soliton whose energy can be determined by integrating the Hamiltonian spatial density over the complete lattice at any given time.…”
Section: Energy Of the Kink Solitonmentioning
confidence: 99%